Let $f: X \rightarrow Y$ be an invertible function. Show that the inverse of $f^{-1}$ is $f$, i.e., $\left(f^{-1}\right)^{-1}=f$.

Vedclass pdf generator app on play store
Vedclass iOS app on app store

Let $f : X \rightarrow Y$ be an invertible function.

Then, there exists a function $g : Y \rightarrow X$ such that $gof = I_X$ and $fog = I_Y$

Here, $f^{-1}=g$

Now,

$gof = I_X$ and $fog = I _{ Y }$

$\Rightarrow f ^{-1}$ of $= I_X$ and $fof -1= I_Y$

Hence, $f^{-1}: Y \rightarrow X$ is invertible and $f$ is the inverse of $f^{-1}$ i.e., $\left(f^{-1}\right)^{-1}=f$

Similar Questions

If $a * b=10$ ab on $Q^{+}$ then find the inverse of 0.01

It is easy to see that $f$ is one-one and onto, so that $f$ is invertible with the inverse $f^{-1}$ of $f$ given by $f^{-1}=\{(1,2),(2,1),(3,1)\}=f$

Which of the following functions cannot have their inverse defined ? (where $[.]\, \to$ greatest integer function)

Let the function $f$ be defined by $f(x) = \frac{{2x + 1}}{{1 - 3x}}$, then ${f^{ - 1}}(x)$ is

Let $f:\left[ {4,\infty } \right) \to \left[ {1,\infty } \right)$ be a function defined by $f\left( x \right) = {5^{x\left( {x - 4} \right)}}$  then $f^{-1}(x)$  is